Theoretical Calculations for Spectroscopic Constants and Anharmonic Force Field of ${\rm N}_2{\rm CO}$ (Journal of Atomic and Molecular Sciences, 2019)
The anharmonic force fields and spectroscopic constants of electronic ground state ($\widetilde{X}^1$A') ofdiazirinone $({\rm N}_2{\rm CO})$ has been investigated employing the DFT (B3LYP, B3PW91, and B3P86) and MP2 methodswith the cc-pVnZ (n = D, T, Q) basis sets. The calculated equilibrium geometries, ground state rotationalconstants, fundamental vibrational frequencies, and equilibrium quartic centrifugal distortion constants of${\rm N}_2{\rm CO}$ are in comparison with experimental or theoretical data. The B3LYP results well reproduce theequilibrium geometries and spectroscopic constants. The anharmonic constants, vibration–rotationinteraction constants, equilibrium sextic centrifugal distortion constants, Coriolis coupling constants, cubicand quartic force constants of ${\rm N}_2{\rm CO}$ are theoretically predicted. The results show that DFT methods canafford more reliable theoretical values than MP2 method.
Keywords: Spectroscopic constant; anharmonic force field; ab initio calculation; diazirinone